Policy mixes for more vital legume value chains: Evaluation across competing policy frames - Kaljonen, Minna; Ott, Anna; Huttunen, Suvi; Kuusela, Assi-Jutta; Lonkila, Annika (The International Journal of Sociology of Agriculture and Food, 2021)
Legumes receive increasing attention in sustainability transition research as they can contribute to more sustainable food systems. Previous research has established the need for policies relating to both production and consumption to tackle the marginalisation of legumes in European cropping systems and diets. In this paper, we apply the policy mix framework to food system transition and develop it further into an interpretive policy mix framework to evaluate policy mixes for more vital legume value chains. The interpretive policy mix framework facilitates a better understanding of competing policy frames in designing more consistent, coherent, and comprehensive policy mixes for transitions. The paper analyses three competing policy frames promoted by the food system actors, who are engaged in the development of legume production and consumption in Finland. A comparative analysis of the frames highlights that the policy objectives do not align well; currently, there is no shared understanding among food system actors of what kind of policy mix is needed for more vital legume value chains. The results emphasise networking as a key element in building more coherent policy mixes. The paper shows how the interpretive policy mix framework can support in this endeavour by unveiling conflict lines and possible compromises between the different policy frames.